2021
DOI: 10.1021/acscatal.1c03496
|View full text |Cite
|
Sign up to set email alerts
|

CH3-Generating Capability as a Reactivity Descriptor for Metal Oxides in Oxidative Coupling of Methane

Abstract: Methyl radicals (CH3 •) are the key intermediates in the heterogeneous–homogeneous reaction processes of catalytic oxidative coupling of methane (OCM). Here, by applying in situ synchrotron-based vacuum ultraviolet photoionization mass spectrometry, we quantitatively detected CH3 • being desorbed from various metal oxides and validated the CH3 •-generating capability as an effective descriptor for the catalytic performance of the metal oxides in OCM. It is found that the C2 yield is linearly correlated to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 44 publications
3
28
0
Order By: Relevance
“…Moreover, the role of Mn still remains an open question in OCM studies. ,, For instance, there has been reports on not only the positive effect in Mn-Na 2 WO 4 /SiO 2 and K x MnO y /SiO 2 but also the negative effect in the La 2 O 3 - or MgO-based catalyst . Because under the OCM the following occur: (i) C 2 production is influenced not only via the surface of catalyst but also via the outer surfaces (gas-phase) reaction. (ii) The reaction usually performs under a high reaction temperature above melting points of metal components. (iii) Synergy of components might be different from kinds of support, ,, and the effect of Mn in OCM under operation conditions is still a controversial subject. In other words, it is demonstrated that the HTS data-driven ML approach can aid catalyst investigation without scientists’ experiences and discover the positive fourth element (viz.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the role of Mn still remains an open question in OCM studies. ,, For instance, there has been reports on not only the positive effect in Mn-Na 2 WO 4 /SiO 2 and K x MnO y /SiO 2 but also the negative effect in the La 2 O 3 - or MgO-based catalyst . Because under the OCM the following occur: (i) C 2 production is influenced not only via the surface of catalyst but also via the outer surfaces (gas-phase) reaction. (ii) The reaction usually performs under a high reaction temperature above melting points of metal components. (iii) Synergy of components might be different from kinds of support, ,, and the effect of Mn in OCM under operation conditions is still a controversial subject. In other words, it is demonstrated that the HTS data-driven ML approach can aid catalyst investigation without scientists’ experiences and discover the positive fourth element (viz.…”
Section: Resultsmentioning
confidence: 99%
“…[ 41 ] The C 2 yield was also revealed to be linearly correlated to the amount and the desorption temperature of CH 3 •. [ 42 ] The better OCM catalyst shows stronger CH 3 • intensity and lower CH 3 • desorption temperature. Although the strategy for the development of highly active OCM catalysts would be to promote the formation of CH 3 •, its detection by general spectroscopic techniques is still a problem that should be solved.…”
Section: Resultsmentioning
confidence: 99%
“…30 Reportedly, La 2 O 3 -based catalysts have exhibited the unique character of low-temperature OCM, but multiple-components supported La 2 O 3 catalysts are rarely reported. 31 to 16.7%; however it is important that addition of data from the literature expanded the possible area of elements for M1-M2-M3 component selections. Although element bias is recognized in selected M1-M2-M3 components, another regression of random forest regression (RFR) suggests a different 11 types per 12 validations based on HTE and literature data-driven indirect ML approach.…”
Section: High Throughput Experiments and Machine Learningmentioning
confidence: 99%